The Mediating Role of Psychological Capital in the Relationship between Ethical Leadership and Organizational Citizenship Behavior - Riffut Jabeen; Saba Munir (Journal of Management and Research, 2018)
The basic aim of this paper is to explore the link between Organizational Citizenship Behavior (OCB) and Ethical Leadership with Psychological Capital (PsyCap) as a mediator between them in a developing country. Questionnaire was used as a tool to collect data from 210 white collar employees of different organizations working both in manufacturing and services sectors of the economy of Punjab, Pakistan. The results suggest that Ethical Leadership positively impacts OCB and the PsyCap of employees fully mediates the relationship between OCB and Ethical Leadership. This research shows that organizations can enhance the citizenship of employees’ behavior by setting the ethical behavior of the leaders leading an organization or a group as an example.